PHENOMEN OF THE PARTY IN POWER IN POST-SOVIET POLITICAL SYSTEM. UKRAINIAN SPECIFICS - Краснова, М.Г. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science")
Development of political parties is one of the most important prerequisites for a democratic transformation of the regime in the post-Soviet countries. One of the features of transitional party systems in post-Soviet states has become a phenomenon of the „party of power”. Under the party in power usually means an integration party type, directly created by the political elite and playing the role of the chief representative of its interests in the sphere of public policy. The article examines the conditions leading to the formation of the ruling party after the collapse of USSR. The peculiarities of the construction of the party system and attempts to create efektinoy "party of power" as an independent political force able to effectively influence public policy